Alopecia areata and trichotillomania as anxiety repercussions in a child - Emilly Neves-Souza; Raissa Marques-Galuppo; Palloma Brandão-Grijó (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Alopecia areata (AA) is a non-scarring alopecia due to an immune-mediated damage to the hair follicles. Trichotillomania (TT) is a psychodermatologic disorder characterized by repetitive hair removal. AA and TT are common causes of hair loss in children and can be triggered by anxiety and distressful events. The simultaneous onset of AA and TT in children is rarely reported in the literature. We describe the case of a 9-year-old male child with a 3-month history of hair loss. The clinical history associated with a detailed trichoscopy led to the diagnosis of concomitant AA and TT.